KEBIJAKAN FORMULASI KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA ANAK - Satriana, I Made Wahyu Chandra (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 3 (2013), 2013)
The discussion on this journal raised regarding policy formulation Restorative Justice in the Criminal Justice System Children . The objectives of this research that in order to properly analyze the basic ideas contained in restorative justice , to do with children in conflict with the law and to analyze policy formulation set forth in the Law. 11 2012 on the Criminal Justice System Kids for restorative justice to children in conflict with the law . While this type of research used in scientific journals this is the kind of normative legal research , because it is based on the assessment that there is a conflict between the norms of Law. 11 of 2012 on the Criminal Justice System Children with the norms contained in the draft - Criminal Code ( Criminal Code ) . In this case the unlawful act committed by the child who has not reached the age of 18 (eighteen years ) diversion efforts which have the purpose for the creation of a balance between the interests of focus and attention to the perpetrator and the victim also impact the completion of the criminal case that happens in the community to ensure and protecting children and their rights in order to live , grow, develop and participate optimally in accordance with the dignity of humanity , as well as protection from violence and discrimination .
Keywords: Policy Formulation; Restorative Justice; Child Protection